Bcl-2 Regulates HIF-1α Protein Stabilization in Hypoxic Melanoma Cells via the Molecular Chaperone HSP90 - Trisciuoglio, Daniela (Public Library of Science, 2010)
BACKGROUND: Hypoxia-Inducible Factor 1 (HIF-1) is a transcription factor that is a critical mediator of the cellular response to hypoxia. Enhanced levels of HIF-1α, the oxygen-regulated subunit of HIF-1, is often associated with increased tumour angiogenesis, metastasis, therapeutic resistance and poor prognosis. It is in this context that we previously demonstrated that under hypoxia, bcl-2 protein promotes HIF-1/Vascular Endothelial Growth Factor (VEGF)-mediated tumour angiogenesis. METHODOLOGY/PRINCIPAL FINDINGS: By using human melanoma cell lines and their stable or transient derivative bcl-2 overexpressing cells, the current study identified HIF-1α protein stabilization as a key regulator for the induction of HIF-1 by bcl-2 under hypoxia. We also demonstrated that bcl-2-induced accumulation of HIF-1α protein during hypoxia was not due to an increased gene transcription or protein synthesis. In fact, it was related to a modulation of HIF-1α protein expression at a post-translational level, indeed its degradation rate was faster in the control lines than in bcl-2 transfectants. The bcl-2-induced HIF-1α stabilization in response to low oxygen tension conditions was achieved through the impairment of ubiquitin-dependent HIF-1α degradation involving the molecular chaperone HSP90, but it was not dependent on the prolyl hydroxylation of HIF-1α protein. We also showed that bcl-2, HIF-1α and HSP90 proteins form a tri-complex that may contribute to enhancing the stability of the HIF-1α protein in bcl-2 overexpressing clones under hypoxic conditions. Finally, by using genetic and pharmacological approaches we proved that HSP90 is involved in bcl-2-dependent stabilization of HIF-1α protein during hypoxia, and in particular the isoform HSP90β is the main player in this phenomenon. CONCLUSIONS/SIGNIFICANCE: We identified the stabilization of HIF-1α protein as a mechanism through which bcl-2 induces the activation of HIF-1 in hypoxic tumour cells involving the β isoform of molecular chaperone HSP90.